Alum: an efficient catalyst for one-pot synthesis of alpha-aminophosphonates - Sonar, Swapnil S.; Shelke, Kiran F.; Kakade, Gopal K.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Chinese Chemical Letters, 2009)
Alum (KAl(SO(4))(2)center dot 12H(2)O) is an inexpensive, efficient, non-toxic and mild catalyst for the one-pot synthesis of alpha-aminophosphonates. A three component reaction of an aldehyde/ketone, an an-tine and triethyl phosphite was carried out under solvent-free conditions to afford the corresponding alpha-aminophosphonates in short reaction times and high yields with the green aspects by avoiding toxic catalysts and solvents. (C) 2009 Murlidhar S. Shingare. Published by Elsevier B.V. on behalf of Chinese Chemical Society. All rights reserved.
Keywords: Aldehyde/ketone; alpha-Aminophosphonates; Alum; Amine; Solvent-free; Triethyl phosphite

Alum catalyzed convenient synthesis of quino [2,3-b][1,5]benzoxazepine alpha-aminophosphonate derivatives - Sonar, Swapnil S.; Sadaphal, Sandip A.; Shitole, Nana N.; Jogdand, Nivrutti R.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Bulletin of the Korean Chemical Society, 2009)
We have described an efficient synthesis of quino[2,3-b][1,5]benzoxazepine alpha-aminophosphonate derivatives by the nucleophilic addition of triethyl phosphite to substituted quino[2,3-b][1,5]benzoxazepines promoted by easily available, inexpensive and mild catalyst KAl(SO(4))(2)center dot 12H(2)O (alum). The reactions proceed smoothly at room temperature under solvent-free reaction conditions and providing high yield of product in very short reaction time.
Keywords: 5]benzoxazepine; alpha-Aminophosphonate; Alum; Quino[2.3-b][1; Solvent-free; Triethyl phosphite

Ammonium metavanadate: an effective catalyst for synthesis of alpha-hydroxyphosphonates - Sonar, Swapnil S.; Kategaonkar, Amol H.; Ware, Madhav N.; Gill, Charansingh H.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Arkivoc, 2009)
Ammonium metavanadate (NH(4)VO(3)) is an inexpensive, efficient and mild catalyst for the synthesis of alpha-hydroxyphosphonate derivatives by the reaction of various aryl or heteroaryl aldehydes with triethylphosphite at room temperature. This method affords the alpha-hydroxyphosphonates in short reaction times, under solvent-free conditions, and in high yield.
Keywords: Aldehyde; alpha-hydroxyphosphonate; Ammonium metavanadate (NH(4)VO(3)); Solvent-free; Triethyl phosphite

Microwave assisted convenient synthesis of quino[2,3-b][1,5]benzoxazepines - Sonar, Swapnil S.; Sadaphal, Sandip A.; Pawar, Shivaji S.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Chinese Chemical Letters, 2009)
A convenient synthesis of quino[2,3-b][1,5]benzoxazepines from substituted 2-chloroquinoline-3-carbaldehyde and 2-hydroxyaniline by using stable, non-toxic and inexpensive catalyst 1,8-diazabicyclo-undecan-7-ene (DBU)/silica gel is described. This method affords the quino[2,3-b][1,5]benzoxazepines under the influence of microwave irradiation (360 W) in solvent-free conditions within short reaction times (2-3 min), giving high yields of products (93-96%). (C) 2009 Murlidhar S. Shingare. Published by Elsevier B.V. on behalf of Chinese Chemical Society. All rights reserved.
Keywords: 3-b][1; 5]benzoxazepines; DBU/silica gel; Microwave irradiatiom; Quino[2; Solvent-free

Synthesis and biological evaluation of new 2-chloro-3-((4-phenyl-1H-1,2,3-triazol-1-yl)methyl)quinoline derivatives via click chemistry approach - Kategaonkar, Amol H.; Shinde, Pravin V.; Kategaonkar, Atul H.; Pasale, Sharad K.; Shingate, Bapurao B.; Shingare, Murlidhar S. (European Journal of Medicinal Chemistry, 2010)
Synthesis of new 2-chloro-3-((4-phenyl-1H-1,2,3-triazol-1-yl)methyl)quinoline derivatives (4a-h) using 1,3-dipolar cycloaddition (click chemistry) reaction of 3-(azidomethyl)-2-chloro-quinoline derivatives (3a-h) with phenyl acetylene in the presence of Cu(I) catalyst has been achieved in very high yield. These molecules were evaluated in vitro for their antifungal and antibacterial activity. Most of the compounds exhibited significant antifungal and antibacterial activity against all the tested strains. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: 1; 2; 2-Chloro3-formyl quinoline; 3-Triazole; Antibacterial; antifungal; Click chemistry